PENGARUH PELAPORAN KEUANGAN DI INTERNET TERHADAP REAKSI PASAR (Studi Empiris pada Perusahaan yang Terdaftar di Indeks Kompas 100 Periode 2011) - Herdhita Akhiruddin; Sutris no (Jurnal Ilmiah Mahasiswa FEB, 2012)
The purpose of this research is to get empirical evidence about the impact of internet financial reporting toward the market reaction that indicated on abnormal stock return, also to get empiric evidence occurrence on abnormal stock return during financial information publication and about the difference between the abnormal stock return before and after financial information published on the company’s website. This research use 58 companies which list on Indeks Kompas 100 in the year of 2011 as sample and selected by purposive sampling. This research testing three hypothesises using simple regression, one sample t-test, and wilcoxon signed rank test. The result of this research indicate that degree of financial information disclosure presented on the website is not has impact toward the market reaction. On the other side, this research also indicate the occurrence of abnormal stock return and indicate that there is difference between abnormal stock return before and after financial information published on the company’s website.   Keywords: Internet Financial Reporting, Degree of Financial Information Disclosure, Abnormal Stock Return.